Financial Inclusion, Household Decision-making and Child Health Outcome in Nigeria - Akeju, Kemi Funlayo (Innovation Journal of Social Sciences and Economic Review, 2024)
This study aims to investigate the impact of financial inclusion and household decision-making on child health outcomes in Nigeria. Specifically, it explores how financial inclusion—measured through mobile phone usage for financial transactions, bank account ownership, and mobile digital payment methods—interacts with women's decision-making power regarding earnings and household purchases to influence child health. Using data from the 2018 IPUMS-NDHS dataset, the analysis considers both rural and urban divides to assess disparities in financial inclusion and its effects on child mortality. The study employs logistic regression analysis to examine the relationship between financial inclusion, household decision-making, and child health. The findings reveal that households with mobile phones for financial transactions have significantly lower odds of child mortality, while bank account ownership has no significant effect. Regional disparities are apparent, with women in rural areas more likely to face financial exclusion and associated negative health outcomes for their children. Additionally, the study finds that women who have decision-making power over household purchases are less likely to experience child mortality in their households. In conclusion, the study emphasizes the need for financial empowerment of women as a critical strategy to improve family well-being and reduce child mortality. Expanding access to mobile financial platforms and enhancing women's decision-making authority are recommended to promote better health outcomes for children in Nigeria.
Keywords: Financial inclusion; household decision making; child health; child mortality; women empowerment; Nigeria